Macrobrachium rosenbergii De Man nodavirus recombinant capsid protein production and its interactions with RNA - Goh, Zee Hong (2015)
Macrobrachium rosenbergii nodavirus (MrNv) is a causative agent of white tail disease (WTD) causing nearly 100% mortality in post-larvae of giant freshwater prawns. In 2012 the major farming areas in Malaysia were found to be infected by MrNv but till now information on the Malaysian isolate MrNv is still unavailable in the NCBI database and studies of this newly emerged member of the Nodaviridae family were not in depth. Studies on the other members of the Nodaviridae family revealed that the RNA binding site is important for virus assembly and removal of this region inhibits the virus maturation. Therefore, researches were conducted to identify the Malaysian MrNv capsid sequence, structural morphologies, nucleic acid contents and the RNA binding site of this virus. In this study, MrNv was isolated from infected prawns obtained from a prawn farm in Negeri Sembilan, Malaysia. Prawn muscle tissues were screened with PCR to detect MrNv. The nucleotide sequence of the MrNv capsid gene isolated from a Malaysian isolate was sequenced and later compared with those available in the NCBI database. Phylogenetic analysis of MrNv capsid protein revealed that the Malaysian isolate was closely related to the Chinese isolates. The coding region of MrNv capsid protein was cloned into pTrcHis2-TOPO expression vector and introduced into Escherichia coli TOP10 cells. The recombinant capsid protein of MrNv containing a His-tag was purified by using immobilized metal affinity chromatography (IMAC). The purified capsid protein was analysed using transmission electron microscopy (TEM), dynamic light scattering (DLS) and sucrose density gradient ultracentrifugation, which revealed the formation of virus-like particles (VLPs) of about 30±3 nm in diameter. RNA molecules were found to be encapsidated inside the cavity of MrNv VLPs which suggested that VLPs resembled the native virus. Amino acid sequence analysis of the MrNv capsid protein revealed that 8 out of 10 amino acids located at residues 20th to 29th are positively-charged suggesting RNA binding region is located in this region. Deletion mutagenesis and amino acid substitutions of the positively-charged amino acids located at the N-terminal end of the MrNv capsid protein were performed to determine the RNA binding region. A total of seven mutants were created with different deletion and point mutations starting from residues 1 to 29 of the N-terminal end of the MrNv capsid protein. All the mutants were shown to assemble into VLPs ranging from 18 to 34 nm in diameter. Mutants with the positively-charged amino acids deleted, namely 29ΔMrNvc and 20-29ΔMrNvc did not contain RNA molecules in their VLPs. A point mutation mutant,namely K20R21R22K23R24A, showed a significantly lower amount of RNA molecules compared with that of mutant R26R27R29A, suggesting that the five positively-charged amino acids residues at positions 20 to 24 play an important role in RNA binding. This study showed the positively-charged amino acids at positions 20 to 29 of the capsid protein are the RNA binding site of MrNv. In conclusion, the nucleotide sequence of Malaysian MrNv capsid gene was determined and showed high similarity with the Chinese isolates. The recombinant MrNv capsid protein produced in bacteria was able to assemble into VLPs which resembled the native virus. The RNA binding site of the capsid protein was identified and located at position 20th to 29th. Removal of this region did not affect virus assembly suggesting that the presence of the assembly domain. This information is useful for the development of a vaccine against MrNv and its structural analysis.